Review of Thomas Goldsmith, ed. 2004. The Bluegrass Reader. Urbana: University of Illinois Press - Jonathan T. King (Current Musicology, 2003)
In a world of increasingly uncertain American identity, it is hardly surprising that an interest in bluegrass music, so tied to notions of white America, should be enjoying a revival. Editor Thomas Goldsmith’s The Bluegrass Reader is the latest addition to a small canon of historical literature that is beginning to coalesce in this environment. Rather than aim for historical definitiveness, as was the case with Tom Ewing’s Bill Monroe Reader (2000), Goldsmith widens his scope to include many forms of documentation including promotional materials, record and CD liner notes, interviews, academic articles, newspaper and magazine articles, program notes, speech transcripts- even a record review parody. The result is a subjective, impressionistic collage of material that breaks little new theoretical ground, but assembles a great deal of essential historical information, representing many facets of the bluegrass universe. For this effort, Goldsmith was recently awarded the International Bluegrass Music Association’s 2004 award for Print Media Personality of the Year.